Association between opioid prescription profiles and adverse health outcomes in opioid users referred for sleep disorder assessment: a secondary analysis of health administrative data - Kendzerska, Tetyana; Malhotra, Atul; Gershon, Andrea S.; Povitz, Marcus; McIsaac, Daniel I.; Aaron, Shawn D.; Bryson, Gregory L.; Talarico, Robert; Godbout, Michael; Tanuseputro, Peter; Chung, Frances (Frontiers in Sleep, 2023)
Background: Information is needed to guide safe opioid prescribing in adults referred for a sleep disorder assessment. Previous studies have shown that individuals referred for a sleep disorder assessment have a higher likelihood of long-acting opioids and higher opioid dosages prescription than the general population, suggesting that these individuals are more at risk for opioid-related adverse health consequences. Methods: We included all adults who underwent a diagnostic sleep study (index date) in Ontario, Canada, between 2013 and 2016 (n=300,663) and filled an opioid prescription overlapping the index date (n=15,713). Through provincial health administrative databases, individuals were followed over time to assess the association between opioid use characteristics and one-year all-cause mortality, hospitalizations and emergency department (ED) visits, and opioid-related hospitalizations and ED visits within extended follow-up to 2018. Results: Controlling for covariates, chronic opioid use (vs. not) was significantly associated with increased hazards of all-cause mortality (adjusted hazard ratio [aHR]: 1.84; 95% confidence interval [CI]: 1.12-3.02), hospitalization (aHR: 1.14; 95% CI: 1.02-1.28) and ED visit (aHR: 1.09; 95% CI: 1.01-1.17). A higher opioid dosage (morphine equivalent daily dose [MED] >90 vs. ≤90 mg/day) was significantly associated with increased hazards of all-cause or opioid-related hospitalization (aHR:1.13; 95% CI: 1.02-1.26 and aHR: 2.27; 95% CI: 1.53-3.37, respectively). Morphine or hydromorphone prescription (vs. oxycodone) was significantly associated with an increased hazard of all-cause hospitalization (aHR: 1.30; 1.07-1.59 and aHR: 1.43; 95% CI: 1.20-1.70, respectively). Hydromorphone or fentanyl prescription (vs. oxycodone) was significantly associated with an increased hazard of opioid-related ED visit and/or hospitalization (aHR: 2.28, 95% CI: 1.16-4.47 and aHR: 2.47, 95% CI: 1.16-5.26, respectively). Conclusion: Findings from this retrospective study may inform the safe prescribing of opioids in adults referred for a sleep disorder assessment.